2017
DOI: 10.1038/s41598-017-18289-8
|View full text |Cite
|
Sign up to set email alerts
|

Orientation in Virtual Reality Does Not Fully Measure Up to the Real-World

Abstract: Adult participants learned to reorient to a specific corner inside either a real or virtual rectangular room containing a distinct featural object in each corner. Participants in the virtual-reality (VR) condition experienced an immersive virtual version of the physical room using a head-mounted display (HMD) and customized manual wheelchair to provide self-movement. Following a disorientation procedure, people could reorient by using either the geometry of the room and/or the distinct features in the corners.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 29 publications
3
38
1
3
Order By: Relevance
“…The combined usage of a fully instrumented treadmill, wearable sensors, and an adequately immersive VR system to investigate real-time disorientation among older participants and patients with dementia during active navigation is, to the best of our knowledge, unprecedented. Previous studies that investigated spatial orientation [ 38 - 40 ] and navigation memory [ 20 , 41 ] have relied mostly on VR systems in which navigation or interaction with the VR environment was passively based on the use of control objects (eg, joystick, mouse). This, however, further limits the ecological validity of such setups, as the locomotion aspect of real-world navigation was apparently lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The combined usage of a fully instrumented treadmill, wearable sensors, and an adequately immersive VR system to investigate real-time disorientation among older participants and patients with dementia during active navigation is, to the best of our knowledge, unprecedented. Previous studies that investigated spatial orientation [ 38 - 40 ] and navigation memory [ 20 , 41 ] have relied mostly on VR systems in which navigation or interaction with the VR environment was passively based on the use of control objects (eg, joystick, mouse). This, however, further limits the ecological validity of such setups, as the locomotion aspect of real-world navigation was apparently lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the erroneous turns supports better knowledge transfer from the RE to the VE as well. Spatial knowledge acquisition in the RE may differ from that in the VE; this may explain the difference of the knowledge transfer [27]. To show such results with statistical rigor, a larger data sample is needed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has recently been shown that participants rely more on distinct features (i.e. landmarks) than on the geometrical layout when asked to reorient themselves in a virtual room using an HMD in combination with a manual wheelchair as compared with navigation in a real room (Kimura et al, 2017).…”
Section: Navigation In Vr Versus Navigation In the Real Worldmentioning
confidence: 99%